Hubungan Faktor Sanitasi Lingkungan dengan Kejadian Stunting pada Balita Usia 6-59 Bulan di Kota Pekalongan Tahun 2023 - Yuniastuti, Ari; Hidayah, Isti; Susanti, R.; Pratikwo, Suryo (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
Stunting is a chronic nutritional problem caused by low intake of nutritious food, poor sanitation, and a long history of disease infection. One of the indirect factors causing stunting is water, sanitation and hygiene (WASH). Pekalongan as the city of batik, it is possible that batik industry waste containing heavy metals can disrupt the growth of children. The purpose of this study is to analyze the factors of environmental sanitation association incidence of stunting among children in Pekalongan. This research is an analytic study with a case-control study design. The population in this study were mothers who had toddlers aged 6-59 months with a total sample of 177 respondents. The sampling technique in this study is a non-probability sampling method, namely purposive sampling. Univariate bivariate and multivariate analysis with SPSS 20.0. The results of statistical tests showed that there was a relationship between Sewage (p=0.000; OR=5,096), light intensity (p=0.000; OR=9,404), vent area (p=0.000; OR=9.941), and the habit of opening windows (p=0.000; OR=27,215) with stunting. The prevalence of stunting in the city of Pekalongan is related to sewage ownership, lighting, ventilation and the habit of opening windows. It is suggested that the Pekalongan government use the Community Based Total Sanitation (CBTS) program to empower the community with regard to environmental sanitation. Keywords: Stunting, WASH, sanitation.